Queer English Language Teacher Identity: A Narrative Exploration in Colombia - Lander, Roderick (Profile: Issues in Teachers' Professional Development, 2018)
This article presents partial results of research exploring links between language teacher identity and queer identity in English language teachers working in Colombia. Three gay male teachers participated in a narrative research project framed within a poststructural perspective on identity. I conducted and recorded semi-structured interviews with the participants and then carried out a thematic analysis of these interviews which led to the emergence of three main themes. Here, I present the most prevalent theme, that of being a gay language teacher in the Colombian context which reveals that the participants all live their queer identity alongside their language teacher identity with ease although they do recount instances of homophobia which have impacted their day-to-day lives and their careers.